Effect of strain localization on fatigue properties of precipitation-hardened steel with an arbitrarily length crack. (February 2021) - Verma, Virendra Kumar; Gopalakrishnan, C.K.; Hamada, Shigeru; Yokoi, Tatsuo; Noguchi, Hiroshi
Graphical abstract: Highlights: Fatigue limit properties of two precipitation-hardened steels are compared. Steels having similar properties other than strain localization are prepared. Superiority of the fatigue limit alters depending on the initial crack size. Strain localization and plasticity-induced crack closure are deciding parameters. Strain localization influences notch sensitivity. Abstract: The present study deals with fatigue crack propagation and fatigue limit properties of two precipitation-hardened steels. One steel is more susceptible to strain localization than other. Both steels have similar tensile and micro-hardness properties. The fatigue properties are compared for a plain specimen, a specimen with a short crack and with a long crack. Effect of strain localization on fatigue properties of precipitation-hardened steel with an arbitrarily length crack is discussed with the help of plasticity-induced crack closure. The superiority of fatigue limit for precipitation-hardened steel depends on the initial crack size, and the strain localization influences notch sensitivity.